2020
DOI: 10.1155/2020/3760375
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Iodine Status on the Risk of Thyroid Nodules: A Cross-Sectional Study in Zhejiang, China

Abstract: Objective. The aim of this study was to explore whether iodine nutrition is associated with the risk of thyroid nodules among adult population in Zhejiang Province, China. Methods. A cross-sectional study was conducted in the general population aged 18 years or older. A total of 2,710 subjects received physical examination, questionnaires, and thyroid ultrasonography. Urinary iodine concentration (UIC) and thyroid hormone levels were measured and documented for each subject. 4 multiple logistic regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…The incidence of thyroid nodules was 9.45% in the present study, which was slightly lower than that in the coast of China (15.5%) [15] and Germany (23.4%) [16]. Several epidemiological studies have demonstrated that the incidence of thyroid nodules increased with age because of degenerative changes in thyroid [16,17].…”
Section: Discussioncontrasting
confidence: 56%
“…The incidence of thyroid nodules was 9.45% in the present study, which was slightly lower than that in the coast of China (15.5%) [15] and Germany (23.4%) [16]. Several epidemiological studies have demonstrated that the incidence of thyroid nodules increased with age because of degenerative changes in thyroid [16,17].…”
Section: Discussioncontrasting
confidence: 56%
“…Among 595 controls, 421(70.8%) patients had thyroid nodule. Epidemiologic studies have reported both positive 31 and inverse 15 , 32 associations between iodine excess and the risk of thyroid nodules, and one Korean study reported higher iodine intake in patients with thyroid nodules than in general population 33 . If we assume our control group had a higher intake of iodine than general population, we might have underestimated the true association.…”
Section: Discussionmentioning
confidence: 99%
“…During that same time period, some scholars observed an increasing trend in the incidence of thyroid nodules and thyroid cancer, and they suggested that salt iodization was a risk factor for the occurrence and development of thyroid nodules [12,13]. However, some scholars offered different viewpoints [14]. Chen et al found that even with salt iodization, the intake of iodine in Zhoushan, China, is still insufficient, and salt iodization is necessary for inland areas [9].…”
Section: Introductionmentioning
confidence: 99%